Perspectives on Music Pedagogy in Informal, Performance-Based Learning - Riyan Hidayatullah (Universitas Negeri Surabaya, 2023)
Music learning practices in formal settings, for example, in the classroom, generally apply structured and systematic curriculum-based learning strategies. The entire learning process has generally been organized and implemented with guidance and supervision by the teacher. In Indonesia, music learning in formal schools still applies the standardization of Western music theory. In fact, music learning practices that offer local pedagogical values provide a very diverse portrait. In higher education, music learning that applies local pedagogy has been going on for some time. The Music Education Study Program (PSPM) of Lampung University is one of the tertiary educational institutions that has implemented music learning practices based on local pedagogy. Learning practices that are also performance-based are carried out with